TAXONOMY OF SOCIAL WASPS OF THE POLlSTINE TRIBE ROPALlDIINI (HYMENOPTERA: VESPIDAE) IN THE EASTERN PART OF THE LESSER SUNDA ISLANDS - Jun-ichi Kojima; Fuki Saito; Lien T. P. Nguyen; Rosichon Ubaidillah; Sri Hartini (Treubia, 2004)
The taxonomy of social wasps of the poiistine tribe Ropalidiini in the eastern part of ti,e Lesser Sunda Islands (viz., Sumba, Flores and Timor as included major islands) was studied based mainly on specimens recently collected by ourselves and those deposited in the Museum Zoologicum Bogoriense, Bogor. Parapolybia varia (Fabricius) and 11 species of Ropalictia are recognized ill tile region and their faunal characteristics are discussed. Nomenclatural changes included are: synonymy of Ropalidia laticincta floresinana van der vecht, 1962 under R. laticincta van der vecht, 1962; synonymies of Icaria nigroplagiata Cameron, 1900, R. mathematica binotata uau der vecin, 1941 and R. mathematica sumbaensis van der vecht, 1962, all under R. mathematica (Smith: 1860); revised status of R. socialis trimarulata van der vecht, 1962, and R. variegata dichrorna van der vecht, 1941, both being raised to species milk. New locality records are R. cyathiformis from Lombok and Flores Islallds, R. laticincta from Sobu (or Sawu) Island, R. rufoplagiata (Cameron) from Timor Island, and R. javanica van der vecht from Sumbawa island.